A5.22 Membrane-Bound and Soluble Baff Expression by Human Rheumatoid Fibroblast-Like Synoviocytes in Response to TLR Stimulation. (25th February 2013) - Kam, NW; Filer, A; Buckley, C; Bombardieri, M; Pitzalis, C
Abstract : Background and Objectives: B cell activating factors of TNF family (BAFF) is associated with the survival and maturation of B cells. BAFF is widely expressed in the rheumatoid arthritis (RA) synovium which is characterised by the presence of synovial niches of autoreactive B cells and sustain in situ autoantibody production. Importantly, B cell niches remain functional in the RA-SCID model in the absence of recirculating cells, suggesting that autocrine mechanisms support ongoing B cell activation in the RA synovium. BAFF exerts its functional role both as a membrane bound protein and in soluble form. Here we investigated whether resident stromal cells in the RA synovium, synovial fibroblasts (RASF), are capable of producing either forms of BAFF and thus contribute to local B cell activation. Methods: mRNA BAFF in RASF stimulated with TLR2, TLR3 and TLR4 ligands was assessed by quantitative Taqman PCR RA dermal fibroblasts (RADF) and osteoarthritis SF (OASF) were used as controls. The cytoplasmic, membrane bound and/or soluble forms of BAFF were investigated by 1) Western blot using total and membrane-enriched protein extracts, 2) flow cytometry, 3) ELISA and 4) immunocytochemistry. Results: In vitro stimulation of TLR3, and to a significantly lesser extent TLR4, but not TLR2 on RASF led to strong induction of BAFF mRNA. In response to TLR3, soluble BAFF was time-dependently released in the supernatant of RASF (~600 pg/ml) and, to a lesser extent, OASF and RADF. RASF constitutively expressed both cytoplasmic and membrane bound BAFF as demonstrated by WB, FACS and immunocytochemistry which was upregulated upon TLR3 stimulation and was significantly increased as compared to RADF. Conclusions: Here we provide conclusive evidence that SF in the RA synovium are a pivotal source of the B cell survival factor BAFF at both mRNA and protein level. In addition to their significant constitutive expression, RASF can further up-regulate cytoplasmic, membrane-bound and soluble BAFF in response to TLR3 stimulation. Overall, our data strongly support a fundamental role for RASF in sustaining functional B cell activation and antibody production in the inflamed RA synovium.